Penggunaan Media Sosial untuk Berbelanja Online Saat Pandemi Covid-19 - Alhapen Ruslin Chandra; Afifah Afifah; Yudhytia Wimeina; Abdiani Khairat (Universitas Medan Area, 2020)
The spread of the Covid-19 virus has limited consumers face-to-face transactions. It is an opportunity for increasing social media usage for online purchasing. This study aims to determine how consumers use social media applications on their smartphones to purchase groceries online during a period of large-scale social distancing due to the Covid-19 outbreak. By using PLS-SEM, this study examines the influence of usefulness, ease of use, social, and friends on the attitude of using social media applications on smartphones towards intention to purchase groceries online. This study found that perceived usefulness and ease of use had a positive effect on attitudes towards using social media applications on smartphones. There was a positive influence of social on attitudes towards the use of social media applications. However, friends did not affect attitudes towards the use of social media applications on smartphones. Attitudes towards the use of social media applications significantly influenced the intention to purchase online